Participation of Math Students in Online and Face-to-Face Hybrid Mathematics Instruction - Balayan, Roel; Oliveros, Rodora T.; Tagalog, Larex B. (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
Blended hybrid mathematics instruction offers the flexibility of online learning and the engagement of face-to-face interaction. However, research on student participation in these learning environments needs to be improved. This study investigated the dynamics of student participation, focusing on four key dimensions: conceptual understanding, mathematical communication, problem-solving, and critical thinking and analysis. A survey of 158 BS Mathematics students revealed that online learners tended to exhibit a higher level of conceptual understanding. At the same time, face-to-face interactions enhance problem-solving skills and stimulate more remarkable development of critical thinking and analytical abilities. Mathematical communication skills were somewhat constrained in both settings, with face-to-face students displaying slightly higher participation. These findings underscore the importance of considering the diverse dimensions of student participation when delivering online and hybrid mathematics courses. Educators should provide opportunities for students to hone and cultivate essential skills across online and face-to-face contexts, thus enriching their learning experience.